Cosmopolitanism and National Identity - Abuzarov, Namig (Scholarya Demo Journal of Ruby, 2019)
The acceleration of globalization has brought the discussion oncosmopolitanism back. Discussions and studies on cosmopolitanism havepredominantly focused on two aspects: political and legal. Legalcosmopolitanism is also known as moral cosmopolitanism. In this work thelegal (ethical) cosmopolitanism has been analyzed in terms of values. It wasalso discussed on the theoretical level how well the national identity isappropriate to cosmopolitan values. The work was also focused on the problemof cosmopolitanism, national affiliation and patriotism. It also analyzed the roleof values such as evaluative standards in the cosmopolitan environment. Theresearch allows us to argue that western values are closer to cosmopolitanism.However, it is not the case in eastern, especially in Islamic context. For Islamicnations religion is one of core segments of their national identity. It playscentral and indispensable role in shaping Islamic nations’ identities.